Regeneration Technique of Bamboo Species through Nodal Segments: A Review - Suwal, Meena Maiya; Lamichhane, Janardan; Gauchan, Dhurva Prasad (Nepal Journal of Biotechnology, 2020)
Micropropagation is an alternative technique to propagate at large scale plants to meet global plant demand. Various researchers have worked on the micropropagation technique to regenerate bamboo species by using nodal segments from years. Contamination, browning, necrosis, and acclimatization with physiological stress are the extreme problems of the micropropagation technique. But, many numbers of papers have been published on micropropagation of the bamboo species through nodal segments as explants. The proliferation of the bamboo shoots is dependent on the season of collection, size of explants, the position of explants, diversity of plants, concentration and combination of plant growth regulators, most adequate culture medium, environmental condition of the equipment, handling, and individual species. Bamboo is a monocarpic fast-growing, tall perennial grass and having the high potential to generate economic and social benefits. It helps to maintain land patterns and control soil erosion. The long life cycle of the bamboo produces a huge amount of seeds but unfortunately, mostly, they are non-viable. So, bamboos are propagated from vegetative by cutting and air layering. However, these methods are only for a small scale and they also tend to destroy large mother plant stocks and difficult to be transported. So, the in vitro propagation technique is useful to obtain large progenies from desired genotypes. Mostly, BAP and TDZ growth hormones are widely used for shoot multiplication and IBA, NAA and IAA are used for root initiation as per developed protocols in tissue culture for large scale production. This review intends to explore an overview of the recent literature reports to summarize the importance of micropropagation by using nodal segments of bamboo species and factors influencing it.